Procedure for Land Dispute Resolution Through Mediation at the Land Office: A Critical Analysis of Procedural Justice - Rorosati, Renistya Anjening; Iwan, Permadi; Hamidi, Masykur (NEGREI: Academic Journal of Law and Governance, 2023)
This research discusses legal certainty related to the period of out-ofcourt dispute resolution through mediation at the land office and its impact on the protracted mediation process. Legal certainty is a crucial element in dispute resolution to ensure justice and certainty for the disputing parties. Through a normative juridical approach, this research analyzes the laws and regulations governing mediation and its practical implementation at the land office. The findings show that the lack of clarity and certainty in the regulation of the mediation period at the land office leads to an ineffective and time-consuming dispute resolution process. Without a clear time limit, the parties and the mediator cannot resolve cases promptly. This study uses a systematic normative juridical research method to analyze these issues. The conclusion is that existing regulations vary in defining and implementing mediation, highlighting the need for technical guidelines for mediation procedures and rules regarding the implementation period at the National Land Agency to ensure optimal and efficient mediation.